Psychological Values in The Film Layangan Putus by Mommy Eka Nur Prasetyawati Contribution in Teaching Literature in High School - Surismiati, Surismiati; Supriatini, Supriatini; Ismail, Gunawan; Mustopa, Mustopa; Holipah, Holipah (Journal of English Education and Teaching, 2024)
The background of the problem in this research is how the structural aspects of the film Layangan Putus include themes, characterization and characterization, the conflict in the film Layangan Putus and what are the psychologic values in the film Layangan Putus by Mommy Eka Nur Prasetyawati. This study aims to describe structural aspects including themes, characterizations and characterizations, conflicts in Mommy Eka Nur Prasetyawati's Layangan Putus film and to describe psychological values in Mommy Eka Nur Prasetyawati's Layangan Putus film. This type of research is qualitative research and uses descriptive methods. The research data is in the form of sentences, paragraphs, which develop psychological values in the film Layangan Disconnect by Mommy Eka Nur Prasetyawati. The data collection technique in this study, namely, the data collection technique in this study was a literature study technique, namely a technique that uses written sources to obtain data. Researchers analyzed the data by reading the Layangan Putus film as a whole and repeatedly per episode to understand the contents of the film, making a synopsis of the Layangan Putus film to provide an overall picture of the story for both researchers and readers, analyzing per episode the psychological values contained in the film. Layagan Putus, classifying psychological values in Layagan Putus film, describing psychological values in Layagan Putus film, concluding the psychological values in Layagan Putus film and the implications for learning in high school. The conclusion from the analysis of the Putus Layangan Film by Mommy Eka Nur Prasetyawati is that there are several psychological values, namely Developmental psychology includes 3 scenes in episode 10B, episode 2A and episode 2B, Social psychology includes 3 scenes in episode 10B, episode 3A and episode 9B, Educational psychology includes 3 scenes in episode 10B and episode 2A, personality psychology and typology includes 1 scene in episode 4B, psychopathology includes 3 scenes in episode 6B and episode 8B, differential psychology and psychodiognostic includes 3 scenes in episode 10B, episode 9A and episode 3A, criminal psychology includes 3 scenes in episode 9B, episode 8A and episode 8A, Parapsychology includes 2 scenes in episode 9B and episode 3B, Comparative psychology includes 3 scenes in episode 4A, episode 1B and episode 10A, Adjustment psychology includes 3 scenes in episode 10B, episode 10A and 10B episodes.